How to use new antibiotics in the therapy of serious multidrug resistant Gram-negative infections?. Issue 6 (18th December 2022) - Windham, Samuel; Kollef, Marin H.
Abstract : Purpose of review: Multidrug resistant Gram-negative infections are becoming more common and pose a serious threat to both individual patients and the population as a whole. Treatment of these infections can be difficult and result in significant morbidity and mortality. The purpose of this review is to discuss information and strategies for using new antibiotics to combat these infections. Recent findings: Eight new antibiotics represent possible means to treat multidrug resistant Gram-negative infections. Although no new mechanisms of action are present amongst these new antibiotics, novel additions to previously utilized mechanisms have been shown to be viable options for treatment of highly resistant organisms. Summary: The novel antibiotics considered in this review have varying data on their use as empiric treatment of patients at high risk for multidrug resistant organisms and as final therapy for identified multidrug resistant organisms. Cefiderocol, ceftazidime-avibactam, ceftolozane-tazobactam, meropenem-vaborbactam, and imipenem-relabactam have the best support evidence for use in this patient population.